Modeling Adsorption Data of Hydrocarbons on 13X Zeolite using the Gaussian Adsorption Isotherm Model - Taji, Salam Mazen (2013)
A Master of Science thesis in Chemical Engineering by Salam Mazen Taji entitled, "Modeling Adsorption Data of Hydrocarbons on 13X Zeolite Using the Gaussian Adsorption Isotherm Model," submitted in January 2013. Thesis advisor is Dr. Kevin Loughlin. Available are both soft and hard copies of the thesis.